Altered expression of G1/S phase cell cycle regulators in placental mesenchymal stromal cells derived from preeclamptic pregnancies with fetal-placental compromise. Issue 2 (17th January 2017) - Nuzzo, Anna Maria; Giuffrida, Domenica; Masturzo, Bianca; Mele, Paolo; Piccoli, Ettore; Eva, Carola; Todros, Tullia; Rolfo, Alessandro
ABSTRACT: Herein, we evaluated whether Placental Mesenchymal Stromal Cells (PDMSCs) derived from normal and Preeclamptic (PE) placentae presented differences in the expression of G1/S-phase regulators p16 INK4A, p18 INK4C, CDK4 and CDK6. Finally, we investigated normal and PE-PDMSCs paracrine effects on JunB, Cyclin D1, p16 INK4A, p18 INK4C, CDK4 and CDK6 expressions in physiological term villous explants. PDMSCs were isolated from physiological (n = 20) and PE (n = 24) placentae. Passage three normal and PE-PDMSC and conditioned media (CM) were collected after 48h. Physiological villous explants (n = 60) were treated for 72h with normal or PE-PDMSCs CM. Explants viability was assessed by Lactate Dehydrogenase Cytotoxicity assay. Cyclin D1 localization was evaluated by Immuofluorescence (IF) while JunB, Cyclin-D1 p16 INK4A, p18 INK4C, CDK4 and CDK6 levels were assessed by Real Time PCR and Western Blot assay. We reported significantly increased p16 INK4A and p18 INK4C expression in PE- relative to normal PDMSCs while no differences in CDK4 and CDK6 levels were detected. Explants viability was not affected by normal or PE-PDMSCs CM. Normal PDMSCs CM increased JunB, p16 INK4 and p18 INK4C and decreased Cyclin-D1 in placental tissues. In contrast, PE-PDMSCs CM induced JunB downregulation and Cyclin D1 increase in placental explants. Cyclin D1 IF staining showed that CM treatment targeted mainly the syncytiotrophoblast. We showed Cyclin D1-p16INK4A/p18INK4C altered pathway in PE-PDMSCs demonstrating an aberrant G1/S phase transition in these pathological cells. The abnormal Cyclin D1-p16INK4A/p18INK4C expression in explants conditioned by PE-PDMSCs media suggest a key contribution of mesenchymal cells to the altered trophoblast cell cycle regulation typical of PE pregnancies with fetal-placental compromise.